Mating behaviour of ram on exposure to estrous ewes - PATEL, M; DAS, N; PANDEY, H N; YADAV, M C; P S, GIRISH (The Indian Journal of Animal Reproduction, 2007)
The experiment was conducted to study the pattern of rams' mating behaviour and its preferencefor ewe when exposed to multiple estrous ewes. Four rams and four estrous ewes were used for thestudy. Ewes were shorn and brought to estrus artificially. Different mating activities were noted duringone hour mating session. The number of times ewe mated and time spent by ram with ewe were alsonoted to check the order of preference among the available ewes. Courtship activities were found lowwith subsequent ejaculation. Depending upon percentage of mounting sessions, number of mountsper session, number of matings per session and time spent by ram with each ewe; the ewes wereranked I, II, III & IV by allotting marks to each parameter. Ewes A, B, C & D ranked I, II, IV & Illindicating the preferential mating by the ram among available ewes. It was observed that number ofewes mated per session varied and ram's preference was based on number of times the ewe served andvaried from estrus to estrus of the same ewe. It was concluded that preferential mating of rams wasfound among available estrous ewes, which led to uneven distribution of mating. The number of mounts per hour and ejaculation per hour increased when ewe number in the mating pen increased.
Keywords: Estrous; Ewe; Mating; Preference; Ram